1983
DOI: 10.1128/iai.42.2.496-500.1983
|View full text |Cite
|
Sign up to set email alerts
|

Antiactin and antitubulin antibodies in canine visceral leishmaniasis

Abstract: Visceral leishmaniasis, a chronic and often fatal disease, is caused by the protozoan parasite Leishmania donovani. Both specific and nonspecific antibodies are produced in the course of the disease, and autoantibodies may be involved in pathogenesis. Tubulin and actin have been found to be associated with L. donovani. To learn whether antiactin and antitubulin antibodies are present in visceral leishmaniasis, we tested sera from 263 infected dogs by enzyme-linked immunosorbent assay for antibodies to the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The severe form of CanL is characterized by renal damage with glomerulonephritis due to immune complex deposition, but there are findings which propose involvement of some other mechanisms too, like migration of T cells into the glomeruli, participation of adhesion molecules, and diminished apoptosis of cells (28). The antibodies involved in the formation of these immune complexes are unknown, although antiactin and antitubulin antibodies are found in dogs with CanL caused by L. donovani (29). Renal dysfunction could be the only clinical manifestation of the CanL and immunoinduced glomerulonephritis could progress into chronic renal failure (CRF), which is the principal cause of animal death in CanL (1).…”
Section: Introductionmentioning
confidence: 99%
“…The severe form of CanL is characterized by renal damage with glomerulonephritis due to immune complex deposition, but there are findings which propose involvement of some other mechanisms too, like migration of T cells into the glomeruli, participation of adhesion molecules, and diminished apoptosis of cells (28). The antibodies involved in the formation of these immune complexes are unknown, although antiactin and antitubulin antibodies are found in dogs with CanL caused by L. donovani (29). Renal dysfunction could be the only clinical manifestation of the CanL and immunoinduced glomerulonephritis could progress into chronic renal failure (CRF), which is the principal cause of animal death in CanL (1).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several methods of detection such as indirect immunofluorescence and ELISA are currently used [9]; however, these techniques suffer from a relative lack of specificity because of potential cross-reactivities with proteins present in crude parasite extracts used as the source of antigen. In addition to the group formed by Leishmania-specific antigens such as gp63 [13], gp46 [14] and Kmp-11 [15], an additional important group of Leishmania antigens is constituted by evolutionarily conserved proteins like kinesin [16], actin and tubulin [17], acidic P ribosomal proteins [18][19][20], histones [21], and particular heat shock proteins (hsp) [22][23][24][25]. In spite of the sequence conservation of the latter group of proteins, the mapping of their antigenic determinants revealed that the humoral response, in humans and in canine VL, is triggered by regions of the parasite antigens which are Leishmaniaspecific.…”
Section: Introductionmentioning
confidence: 99%
“…In canine leishmaniasis several autoantibodies have been detected such as antinuclear antibodies and autoantibodies against mammalian basal membrane glycoproteins and cerebrosides (PATERAKI et al, 1983).…”
Section: Introductionmentioning
confidence: 99%